How to heal a workplace : tackle trauma, foster psychological safety and boost happiness at work - Howard, Kerry (John Wiley & Sons Australia, Ltd, 2023)
Boost wellbeing and build a robust, productive culture in your workplace Your workplace's most powerful resource is its people. That's why it's critical to balance the needs of your business with the needs of the employees who make that business happen every day. At the heart of the matter is your workplace culture: the environments and relationships that shape your business, whether physical or virtual. How to Heal a Workplace shares the insights and hands-on advice that you need to better understand how your culture impacts your team. You'll learn how to manage interpersonal challenges--and anticipate the impact of policies and procedures--to create a healthier, happier and more productive environment. Drawing on real-world stories from diverse industries, in-demand workplace mental health consultant Kerry Howard shares strategies that will help you: Boost employee wellbeing, and attract and retain staff by supporting their mental health Understand how trauma is caused by everyday events and how this impacts the workplace Combat bullying and harassment and prevent workplace injuries Foster psychological safety, improve communication, and build better relationships between colleagues In How to Heal a Workplace, you'll find the practical advice you need to create a better culture, improve productivity and increase satisfaction across every area of your business.